Self-Adjustment Strategies of International Chain Hotels in Surabaya during the New Normal Era - Yudhiasta, Sheidy (Pusat P2M Politeknik Negeri Batam, 2023)
The Covid-19 pandemic severely impacted Indonesia's tourism industry, resulting in a sharp decline in hotel room occupancy rates in Surabaya. To recover, hotels adopted strategies. This article examines how hotels affiliated with international brand networks coped with the pandemic. The study focuses on Quest Hotel and Holiday Inn Express Surabaya CenterPoint, both renowned for their star ratings and business hotel concept in the city centre. Research revealed a significant drop in room occupancy rates during the pandemic. Strategies included strict adherence to health protocols, salary adjustments without altering service charge calculations, limited use of hotel facilities, showcasing health and cleanliness certifications on promotional materials, flexible booking periods, room price promotions, and non-room product sales. These measures aimed to prioritize guest safety, increase revenue, and adjust to the pandemic's impact. Implementing these adaptations, the hotels aimed to position themselves for recovery and success in the new normal era.